Public Relations Strategy in Creating School Branding Through Social Media - Novita, Putri Dea; Amilda; Atika, Nyimas (Studia Manageria, 2024)
This study discusses the process of public relations strategy to create school branding through social media at SMK Bakti Ibu 3 Palembang. Through a qualitative approach with interview, observation and documentation techniques. In carrying out the school branding strategy, public relations carries out two strategies used in creating school branding through social media using two applications, namely Instagram and Tiktok. The strategies carried out in these two applications are in the form of publication of school activities through social media and activities to build interactions with followers on social media. Publication of activities posted on social media accounts, namely by publicizing various school events, extracurricular activities and student achievements and public relations activities in building interactions with followers on social media accounts by actively participating in replying to followers' comments on social media accounts so that it is hoped that this can establish school closeness with followers on social media in an effort to create school branding. With this strategy, it is expected that the quality, school activities and various school achievements can be known and recognized by the entire community.